The mosquito vectors that sustained malaria transmission during the Magude project despite the combined deployment of indoor residual spraying, insecticide-treated nets and mass-drug administration. - Lucía Fernández Montoya; Helena Martí-Soler; Mara Máquina; Kiba Comiche; Inocencia Cuamba; Celso Alafo; Lizette L Koekemoer; Ellie Sherrard-Smith; Quique Bassat; Beatriz Galatas; Pedro Aide; Nelson Cuamba; et al. (PLoS ONE)
The "Magude project" aimed but failed to interrupt local malaria transmission in Magude district, southern Mozambique, by using a comprehensive package of interventions, including indoor residual spraying (IRS), pyrethroid-only long-lasting insecticide treated nets (LLINs) and mass-drug administration (MDA). Here we present detailed information on the vector species that sustained malaria transmission, their association with malaria incidence and behaviors, and their amenability to the implemented control interventions. Mosquitoes were collected monthly between May 2015 and October 2017 in six sentinel sites in Magude district, using CDC light traps both indoors and outdoors. Anopheles arabiensis was the main vector during the project, while An. funestus s.s., An. merus, An. parensis and An. squamosus likely played a secondary role. The latter two species have never previously been found positive for Plasmodium falciparum in southern Mozambique. The intervention package successfully reduced vector sporozoite rates in all species throughout the project. IRS was effective in controlling An. funestus s.s. and An. parensis, which virtually disappeared after its first implementation, but less effective at controlling An. arabiensis. Despite suboptimal use, LLINs likely provided significant protection against An. arabiensis and An. merus that sought their host largely indoors when people where in bed. Adding IRS on top of LLINs and MDA likely added value to the control of malaria vectors during the Magude project. Future malaria elimination attempts in the area could benefit from i) increasing the use of LLINs, ii) using longer-lasting IRS products to counteract the increase in vector densities observed towards the end of the high transmission season, and iii) a higher coverage with MDA to reduce the likelihood of human infection. However, additional interventions targeting vectors that survive IRS and LLINs by biting outdoors or indoors before people go to bed, will be likely needed to achieve local malaria elimination.